Beyond the numbers budgeting for museum professionals - Zickuhr, Kristine, 1971- (American alliance of museums, 2022)
"The book is particularly suited for staff members in small or medium-sized museums who are interested in understanding and developing basic budgets. It would also serve as a helpful resource for individuals advancing into leadership positions which require stronger administrative skills"--